2020
DOI: 10.1002/app.49907
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of oleylamine modified silica‐reinforced natural rubber composites

Abstract: Oleylamine (OA) modified silica (SiO 2-g-OA) was prepared using γ-(2,3-epoxypropoxy) propytrimethoxysilane (KH560) and OA, silica/natural rubber (NR) and SiO 2-g-OA/NR composites were prepared by mechanical blending in an internal mixer, and SiO 2-g-OA was characterized by Fourier transform infrared spectroscopy, thermal gravimetric analyzer, and contact angle analyzer. The mechanical properties, abrasion resistance, curing characteristics, Payne effect, and morphology of silica/NR and SiO 2-g-OA /NR composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The M L is related to the viscosity of the rubber compounds. The increase in M L was probably due to the PAA- co -PAM chains and the rigid silica particles restricting the motion of the rubber chains [ 64 ]. Moreover, the delta torque (M H -M L ) of the (PAA- co -PAM)-DPNR was higher than that of the DPNR, and the addition of silica presented an increase in the delta torque.…”
Section: Resultsmentioning
confidence: 99%
“…The M L is related to the viscosity of the rubber compounds. The increase in M L was probably due to the PAA- co -PAM chains and the rigid silica particles restricting the motion of the rubber chains [ 64 ]. Moreover, the delta torque (M H -M L ) of the (PAA- co -PAM)-DPNR was higher than that of the DPNR, and the addition of silica presented an increase in the delta torque.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the chemical interfacial interaction also endows the nanocomposite with thermal stability, avoiding a sharp fall of mechanical strength with increasing temperature. Silane coupling agents, such as silane with C C bond, 65,66 silane with a sulfhydryl group [67][68][69] and silane with a polysulfide bond, 70,71 are the most adopted modification reagents. Obviously, the modification process significantly enhances the interfacial interaction between silica and rubber matrices.…”
Section: Silica Modificationmentioning
confidence: 99%
“…Finally, the energy loss of the resultant composites was remarkably decreased. Mei et al 8 reported a way to modify silica via using oleylamine and γ‐(2,3‐epoxypropoxy) propytrimethoxysilane (KH560), and the results demonstrated the lower rolling resistance and better mechanical properties of NR/silica composite were obtained. Others about the hybrid fillers, 9 graft of CB by hyperbranched polymer, 10 polyethylene glycol, 11 and wet masterbatch technology 12 had been mentioned before.…”
Section: Introductionmentioning
confidence: 99%